Oral and Dental Health Knowledge of Nursing and Midwifery Students - ÖZÇELİK, SEMANUR KUMRAL; AKYÜZ, SERAP HATİCE (MARMARA UNIV, INST HEALTH SCIENCES, 2017)
Objective: The objective of this study was to determine Oral and Dental Health (ODH) knowledge of nursing and midwifery students. Methods: This descriptive-type study was conducted on 281 nursing and 200 midwifery students studying at the faculty of health sciences of a state university in Istanbul. Data were collected through a descriptive information form that included ODH behaviors and sociodemographic characteristics of students and an information test regarding students' knowledge of oral and dental health issues. The forms were prepared by the investigators based on the literature. Descriptive statistical analyses and chi-square tests were used to analyze the data. Results: The mean age of the students was 20.47 +/- 1.50 years, and there were 428 (89%) female and 53 (11%) male respondents. A total of 280 (58.2%) of the students had previously received information about ODH, and 170 (35.3%) of all the students claimed that they had obtained information about ODH from the Internet. It was interesting to note that only 68 (14.1%) of the students had regular dental check-ups. The average of accurately answered questions was 59.09% in the information test. How many times a day should teeth be brushed? (97.5%) was the question that was the most frequently answered accurately, followed by Who might have periodontal diseases? (96.3%). The questions with the lowest percentages of accurate responses were What is the right age to start brushing children's teeth? (11%) and Which childhood diseases occurring in pregnancy affect the development of children's teeth? (15.8%). Conclusion: It was concluded that students generally had insufficient ODH knowledge, and this finding indicates the necessity of including ODH programs in the education of healthcare professionals.
Keywords: Oral and dental health; midwifery; nursing; university students; EDUCATION-PROGRAM; CARE; MIDWIVES; DISEASES; CHILDREN; AUSTRALIA; ATTITUDES; CARIES